Dilma Rousseff’s impeachment: analysis of the argumentative strategies of Veja e CartaCapital after the voting at the Lower House - Pozobon, Rejane de Oliveira (2018)
This work analyzes the articles “Folga de 25 votos” by Veja magazine and "Sorriso da Mona Lisa" by CartaCapital magazine, both articles refer to the impeachment process of Dilma Rousseff in the Lower House. Therefore, we are supported by authors such as Foucault , Bourdieu and Charaudeau who discuss discourse and power relations in society. For an approximation with our objects, we are mainly based on Charaudeau that talks about the discourse of the media. The methodology is based on the four argumentative strategies presented by Breton: authority, framework, community and analogy. As a conclusion we observe that the magazines converge when they expose a negative profile of Eduardo Cunha and unpopularity of Michel Temer, however, they differ when they mention other participants of the process such as Dilma Rousseff and Lula.